Method for testing extrudability of epoxy adhesive for prefabricated segment assembly

By using simple consumables such as ring-shaped polytetrafluoro dies and polyester films, the extrusion testing steps are refined, and the problems of poor repeatability and difficult sampling in the prior art are solved, thus achieving more accurate and reliable capabilities Extrusion test results.

CN119413569APending Publication Date: 2025-02-11CHINA ACAD OF BUILDING RES +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411586236.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When the prior art tests the extrusionability of epoxy adhesives for prefabricated segment assembly, the results are poorly repetitive, which affects the accuracy and reliability of the test results. Moreover, sampling of high viscosity adhesives is difficult and it is easy to introduce bubbles. This results in low test results.

Method used

Using simple consumables such as ring-shaped polytetrafluoro molds and polyester films, the test steps for extrusion are refined. By marking the polytetrafluoro mold positions in the center of the polyester film, the sample shape is consistent and in a universal test machine. After applying pressure, the area of ​​the sample is measured and the extrusionability is calculated.

Benefits of technology

It improves the accuracy and reliability of extrudability test results, reduces test costs, simplifies the test methods, and avoids test results deviations caused by irregular sample shape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413569A_ABST
    Figure CN119413569A_ABST
Patent Text Reader

Abstract

The invention relates to a method for testing the extrudability of an epoxy adhesive for prefabricated segment assembly, and belongs to the technical field of material testing. Comprising the following steps: S1, placing a sample preparation device at a specified test temperature for 24 hours; s2, placing the annular polytetrafluoroethylene mold coated with vaseline at the mark of the first circular polyester film, and filling the annular polytetrafluoroethylene mold with the splicing glue sample; s3, slowly and vertically lifting the polytetrafluoroethylene annular mold to obtain a complete cylindrical splicing glue extrudability to-be-tested sample; s4, immediately putting the sample to be tested and the polyester film on a steel bearing plate of a universal testing machine; s5, applying specified pressure to obtain a cake-shaped splicing glue sample; s6, measuring and calculating the extrudability of the splicing glue sample; and S7, repeating the steps, and taking an arithmetic mean value of the extrudability. The problems of accuracy and reliability in the testing process can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a testing method, in particular to a testing method for the extrudability of epoxy adhesive for prefabricated segment assembly, and belongs to the technical field of material testing. Background Art

[0002] Epoxy adhesive for prefabricated segment assembly (hereinafter referred to as splicing adhesive) is a high-performance engineering material widely used in prefabricated concrete segment assembly projects such as bridges and wind turbine towers. In engineering applications, workers often use manual application to apply this material to the concrete end faces to be assembled, and then apply prestress to the concrete segments. This process requires that the applied splicing adhesive overflows from all sides of the concrete end face after being squeezed by external force to ensure that the concrete end face is evenly covered by the splicing adhesive, ultimately ensuring the mechanical properties of the joint. However, when the extrudability is too large, the splicing adhesive may overflow from all sides of the concrete end face, but it is also easy to cause material waste. Therefore, the extrudability of this material is of great practical significance in guiding the research and development and production of production enterprises and actual engineering construction.

[0003] At present, the test method for the extrudability of splicing adhesive can be carried out according to the group standard T / CECS10080-2020 "Epoxy Adhesive for Prefabricated Segment Assembly", T / CEC 5008-2018 "Technical Specifications for Prestressed Prefabricated Concrete Towers of Wind Turbine Generators" and the national standard GB / T 44543-2024 "Epoxy Adhesive for Prefabricated Concrete Segment Assembly". The key elements of the extrudability test are the amount of adhesive used, the pressure, the pressurization time and the test temperature, and the area = πr 2 When the amount of glue used is too large, the pressure applied is too large, and the pressurization time is too long, the measured extrudability will be too large; the test temperature affects the viscosity of the adhesive and thus affects the test results. After comprehensively analyzing the test methods specified in the above standards, we concluded that the existing technology has the following technical difficulties in actual operation:

[0004] T / CECS10080-2020 "Epoxy Adhesives for Prefabricated Segment Assembly" and national standard GB / T44543-2024 "Epoxy Adhesives for Prefabricated Concrete Segment Assembly" stipulate that the sampling volume is 3140mm 3, the corresponding mass of the sample can be calculated by multiplying the density and volume as the mass; but none of them clearly give how to measure the extended area of ​​the sample. The above technical difficulties lead to poor repeatability of the test results, affecting the accuracy and reliability of the test results. T / CEC 5008-2018 "Technical Specifications for Prestressed Prefabricated Concrete Towers of Wind Turbines" proposes to fill the splicing glue sample into an intravenous syringe for sampling, but in actual operation, it is found that for this high-viscosity paste adhesive, filling is extremely difficult, especially after low-temperature treatment, the splicing glue will become more viscous, and the sampling difficulty will be further increased. In addition, high-viscosity adhesives will inevitably introduce bubbles during the filling process, which makes the actual sampling volume low, and ultimately leads to low test results. Summary of the invention

[0005] In view of the above defects or problems in the prior art, the present invention provides a method for testing the extrudability of epoxy adhesive for prefabricated segment assembly, which is used to solve the accuracy and reliability problems of the testing process.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for testing the extrudability of epoxy adhesive for prefabricated segment assembly comprises the following steps:

[0008] S1: Place the components A and B of the splicing glue, two round polyester films of the same size as the steel pressure plate used for pressure application, and a polytetrafluoroethylene ring mold at the specified test temperature for 24 hours; before placing, mark the center of the first polyester film with a polytetrafluoroethylene ring mold;

[0009] S2: Place the polytetrafluoroethylene ring mold coated with vaseline on the mark of the first circular polyester film, fill the polytetrafluoroethylene ring mold with the splicing glue sample after the splicing glue components A and B are evenly mixed, and clean up the excess sample around it after filling;

[0010] S3: Slowly lift the polytetrafluoroethylene annular mold vertically to obtain a complete cylindrical splicing adhesive extrudability test sample;

[0011] S4: Immediately transfer the sample to be tested together with the first polyester film to the steel pressure plate of the universal testing machine so that the first polyester film overlaps the pressure plate;

[0012] S5: After gently placing the second polyester film on the cylindrical splicing adhesive extrudability test sample, start to apply a specified pressure; after maintaining the pressure for 3 minutes, immediately release the pressure to obtain a round splicing adhesive sample;

[0013] S6: Use a vernier caliper to measure the maximum diffusion diameter of the circular splicing glue sample and the diameter in the perpendicular direction, and take the average value r; then according to the area of ​​the circle = πr2 , the extrudability of the splicing glue sample was calculated;

[0014] S7: Repeat the above steps S1-S6 three times. The test results are the arithmetic mean of the extrudability of the splicing adhesive samples in the three tests, and are accurate to square millimeters.

[0015] Furthermore, in step S1, the inner diameter and height of the polytetrafluoroethylene annular mold are both 10 mm.

[0016] Furthermore, the steps S2-S5 are all performed at a specified temperature, and the corresponding temperature is controlled by using an oven and a universal testing machine with a temperature-controlled chamber.

[0017] Furthermore, the universal testing machine includes an upper pressure plate and a lower pressure plate.

[0018] Furthermore, in the step S1, the splicing adhesive components A and B, two circular polyester films of the same size as the steel pressure plate used for pressurization, and a polytetrafluoroethylene annular mold are temperature-controlled in an oven.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention uses reusable annular polytetrafluoroethylene molds, polyester films and other simple consumables that are easily available in the laboratory to refine the test steps of extrudability and reduce the test cost. At the same time, the volume of the fixed polytetrafluoroethylene mold is 3140mm 3 It can effectively avoid the deviation of test results caused by excessive or insufficient splicing glue samples due to improper sampling, and improve the accuracy and reliability of extrudability test results.

[0021] 2. Marking the position of the ring-shaped polytetrafluoroethylene mold in the center of the polyester film in advance can effectively ensure that the sample to be pressed is cylindrical, and a round cake-shaped test sample is obtained after pressure is applied, avoiding the irregular shape of the splicing glue sample when it contacts the polyester film, which causes the irregular round cake pattern after pressure. This is conducive to the subsequent calculation of the extrudability test results by the method of calculating the circle area, thereby improving the accuracy and reliability of the sample test results. At the same time, the simplified test method is easier to promote and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a schematic diagram of a sample preparation apparatus shown in step S1 of the present invention;

[0023] Figure 2 It is a schematic diagram of the polytetrafluoroethylene annular mold of the present invention;

[0024] Figure 3 is a sample schematic diagram corresponding to step S2 of the present invention;

[0025] Figure 4 Schematic diagram of a cylindrical splicing adhesive sample to be tested for extrudability corresponding to step S3 of the present invention;

[0026] Figure 5 This is a schematic diagram of the second polyester film after placement in step S5 of the present invention;

[0027] Figure 6 It is a test schematic diagram of a universal testing machine with a temperature-controlled chamber;

[0028] Figure 7 This is a photo of a round cake-shaped splicing adhesive sample under the specified pressure of 150N and the specified temperature of 15°C of the present invention;

[0029] Figure 8 This is a photo of a round cake-shaped splicing adhesive sample with a specified pressure of 2000N and a specified temperature of 15°C according to the present invention.

[0030] Reference numerals:

[0031] 1: Polyester film; 2: PTFE ring mold; 3: Sample to be tested; 4: Pressure plate; 5: Upper pressure plate; 6: Temperature control chamber; 7: Center position; F: Universal testing machine applies pressure. DETAILED DESCRIPTION

[0032] The following is combined with Figure 1-6 The present invention is further described in detail with specific implementations to facilitate a clear understanding of the present invention, but they do not constitute a limitation on the present invention.

[0033] Example 1

[0034] As attached Figure 1-6 As shown, a method for testing the extrudability of an epoxy adhesive for prefabricated segment assembly in this embodiment includes the following steps:

[0035] S1: Figure 1-2 As shown, place the sample preparation equipment, components A and B of the splicing glue, two round polyester films 1 of the same size as the steel pressure plate used for pressure application, and a polytetrafluoroethylene ring mold 2, at the specified test temperature for 24 hours. Before placing, mark the center position 7 of the first polyester film 1 with the polytetrafluoroethylene ring mold 2. Figure 2 As shown, the inner diameter and height of the polytetrafluoro ring mold are both 10 mm. In step S1, the splicing adhesive components A and B, two circular polyester films 1 of the same size as the steel platen used for pressing, and the polytetrafluoro ring mold 2 are temperature controlled in an oven.

[0036] S2: Figure 3As shown, the polytetrafluoro ring mold 2 coated with vaseline is placed on the mark of the first circular polyester film 1, and the splicing glue sample obtained by evenly mixing the splicing glue components A and B is filled into the polytetrafluoro ring mold 2. After the filling is completed, the excess sample 8 around it is cleaned up.

[0037] S3: Slowly lift the polytetrafluoroethylene annular mold 2 vertically to obtain a complete cylindrical splicing adhesive extrudability test sample 3, such as Figure 4 shown.

[0038] S4: Immediately transfer the sample 3 to be tested together with the first polyester film 1 onto the steel pressure plate 4 of the universal testing machine so that the first polyester film 1 overlaps the pressure plate 4 .

[0039] S5: Figure 5 As shown, the second polyester film 1 is gently placed on the cylindrical splicing adhesive extrudability test sample 3, and then a specified pressure is applied. After constant pressure for 3 minutes, the pressure is immediately released to obtain a round splicing adhesive sample.

[0040] S6: Use a vernier caliper to measure the maximum diffusion diameter of the circular splicing glue sample and the diameter in the perpendicular direction, and take the average value r. Then according to the area of ​​the circle = πr 2 , the extrudability of the splicing glue sample was calculated.

[0041] S7: Repeat the above steps S1-S6 three times. The test results are the arithmetic mean of the extrudability of the splicing adhesive samples in the three tests, and are accurate to square millimeters.

[0042] In this embodiment, steps S2-S5 are all performed at a specified temperature, and the corresponding temperature is controlled by an oven and a universal testing machine with a temperature control chamber 6. Figure 6 As shown, the universal testing machine includes an upper pressing plate 5 and a lower pressure plate 4.

[0043] The following table lists the specific experimental results of two groups of different epoxy adhesives used in this experiment. Each group of epoxy adhesives includes 3 tests, and the arithmetic mean of extrudability is taken, accurate to square millimeters. Among them, d1 is the maximum diffusion diameter of the round cake splicing adhesive sample, and d2 is the diameter of the maximum diffusion vertical direction of the round cake splicing adhesive sample. The method of this embodiment can effectively improve the accuracy and reliability of the extrudability test results.

[0044]

[0045]

[0046] The above is only a preferred embodiment of the present invention, and does not impose any formal limitation on the structure of the present invention. The layout type and the number of uses of the present invention are not limited to this example, and can be optimized and selected according to the actual project. Any modification, equivalent change and decoration of the above embodiment based on the technical principle of the present invention that does not deviate from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for testing the extrudability of epoxy adhesive for prefabricated segment assembly, characterized in that: The steps include: S1: Place the sample preparation equipment including the components A and B of the splicing adhesive, two circular polyester films (1) of the same size as the steel pressure plate used for pressure application, and a polytetrafluoroethylene ring mold (2) at the specified test temperature for 24 hours; before placing, mark the center of the first polyester film (1) with the polytetrafluoroethylene ring mold (2); S2: Place the polytetrafluoroethylene annular mold (2) coated with vaseline on the mark of the first circular polyester film (1), fill the polytetrafluoroethylene annular mold (2) with the splicing glue sample obtained by evenly mixing the splicing glue components A and B, and clean up the excess sample around it after filling; S3: slowly lift the polytetrafluoroethylene annular mold (2) vertically to obtain a complete cylindrical splicing adhesive extrudability test sample (3); S4: Immediately transfer the sample to be tested (3) together with the first polyester film (1) to a steel pressure plate (4) of the universal testing machine, so that the first polyester film (1) overlaps the pressure plate (4); S5: After gently placing the second polyester film (1) on the cylindrical splicing adhesive extrudability test sample (3), a specified pressure is applied; after maintaining the pressure for 3 minutes, the pressure is immediately released to obtain a circular splicing adhesive sample; S6: Use a vernier caliper to measure the maximum diffusion diameter of the circular splicing glue sample and the diameter in the perpendicular direction, and take the average value r; then according to the area of ​​the circle = πr 2 , the extrudability of the splicing glue sample was calculated; S7: Repeat the above steps S1-S6 three times. The test results are the arithmetic mean of the extrudability of the splicing adhesive samples in the three tests, and are accurate to square millimeters.

2. The method for testing the extrudability of epoxy adhesive for prefabricated segment assembly according to claim 1, characterized in that: In the step S1, the inner diameter and height of the polytetrafluoroethylene annular mold are both 10 mm.

3. The method for testing the extrudability of epoxy adhesive for prefabricated segment assembly according to claim 1, characterized in that: The steps S2-S5 are all performed at a specified temperature, and the corresponding temperature is controlled by using an oven and a universal testing machine with a temperature control chamber (6).

4. The method for testing the extrudability of epoxy adhesive for prefabricated segment assembly according to claim 3, characterized in that: The universal testing machine comprises an upper pressure plate (5) and a lower pressure plate (4).

5. The method for testing the extrudability of epoxy adhesive for prefabricated segment assembly according to claim 3, characterized in that: In the step S1, the components A and B of the splicing glue, two circular polyester films (1) of the same size as the steel pressure plate used for pressure application, and a polytetrafluoroethylene annular mold (2) are used as sample preparation tools for temperature control in an oven.

Citation Information

Cited By

  • Testing device for extrudability of epoxy adhesive

    CN120253464A

  • A device for testing the extrudability of epoxy adhesives

    CN120253464B